Conformationally constrained PNA analogues: structural evolution toward DNA/RNA binding selectivity - Kumar, VA; Ganesh, Krishna N. (Accounts of Chemical Research, 2005)
Since its discovery 12 years ago, aminoethylglycyl peptide nucleic acid (aeg-PNA) has emerged as one of the successful DNA mimics for potential therapeutic and diagnostic applications. An important requisite for in vivo applications that has received inadequate attention is engineering PNA analogues for able discrimination between DNA and RNA as binding targets. Our approach toward this aim is based on structural preorganization of the backbone to hybridization-competent conformations to impart binding selectivity. This strategy has allowed us to design locked PNAs to achieve specific hybridization with DNA or RNA with aims to increase the binding strength without losing the binding specificity. This Account presents results of our rationale in design of different conformationally constrained PNA analogues, their synthesis, and evaluation of hybridization specificities.